PENGARUH KEPEMILIKAN MANAGERIAL, PROFITABILITAS DAN KESEMPATAN INVESTASI TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Silfiana, Merlinda (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
This study aims to analyze the managerial ownership, profitability, and investment opportunity set on dividend policy on companies listed in Indonesian Stock Exchange 2009-2013. The variables used are managerial ownership, profitability, market to book value and growth companies. The total of the sample which used in this study is 30 companies. This study uses quantitative approach with multiple regression method. This study found that incompanies listed 2009-2013; managerial ownership, profitability, market to book value and growth companies are simultaneous significantly affect dividend policy. Partially, only market to book value is positive significantly affect dividend policy, and another are managerial ownership and profitability are negative significantly affect dividend policy. While the growth companies is positive not significantly affect dividend policy. Keywords: dividend policy, managerial ownership, profitability, market to book value and growth companies